Direct-to-consumer detection of atrial fibrillation in a smartwatch electrocardiogram: Medical overuse, medicalisation and the experience of consumers. (June 2022) - Shih, Patti; Prokopovich, Kathleen; Degeling, Chris; Street, Jacqueline; Carter, Stacy M.
Abstract: The Apple Watch Electrocardiogram (ECG) is a digital feature that detects signs of atrial fibrillation (AFib), a heart arrhythmia that can lead to stroke. Unlike AFib detection offered in a clinical setting to patients or those at higher risk, the Apple Watch ECG is a direct-to-consumer (DTC) product marketed to the healthy as a self-performed medical test. The feature is incorporated in the design as one of many applications in a multifunctional smartwatch. The Apple Watch ECG signals the movement of consumer wearables into the domain of medical devices, and the highly contested practice of AFib screening. This article examines how this technology produces new avenues for medical overuse among people who are unlikely to gain clinical benefit, and who as active consumers become medicalised via taking part in disease-specific monitoring. Interviews with Apple Watch ECG consumers suggest their strongly trust in the Apple brand is amplified by the promissory quality of screening and technical innovation. What would otherwise be a costly clinical procedure is condensed into an accessible function in a wearable device. Consequently, AFib screening loses its clinical purpose, and is instead refashioned into a component of healthy lifestyle behaviour. Repeat self-screening becomes 'bundled' with similar health monitoring practices routinised in consumer wearables. Active uptake supports a market for the product and adds to the reputation of the Apple brand such that consumers become complicit in legitimising a medical practice that has limited clinical justification. Highlights: Movement of consumer wearables into domain of medical devices signal new routes of medicalisation. Direct-to-consumer AFib screening in a smartwatch drives medical overuse among the healthy. Consumer value technical innovation and promissory quality of screening offered by a trusted brand. Screening in a wearable device is refashioned as part of healthy people's self-monitoring routines. Consumers become complicit in legitimising medical screening with limited clinical utility.